Tailoring of pore structure in mesoporous carbon for favourable flavin mediated interfacial electron transfer in microbial fuel cells. Issue 18 (6th March 2018) - Tang, Wei; Wu, Xiao-Shuai; Qiao, Yan; Wang, Rui-Jie; Luo, Xian
Abstract : Spherical mesopores with large pore width are more favorable to flavin mediated interfacial electron transfer in microbial fuel cells. Abstract : Mesoporous carbon (MC) is supposed to be a good candidate for microbial fuel cell (MFC) anodes as it possesses a large specific area for the redox reaction of the electron shuttles and should deliver high power density. However, the power generation performance of MC anodes is often un-satisfying. It seems that a large portion of the pore surface is not available for anodic redox reaction but the reason is not clear. Here, three MCs with different pore sizes and pore shapes were fabricated and used to explore the effect of the pore structure on the bioelectrocatalysis in Shewanella putrefaciens CN32 MFCs. It is interesting that MC with 40–60 nm spheric pores (MC-III) possesses superior bio-electrocatalytic performance to the CMK-3 (MC-I with 3 nm channel like pores) and the one with 14 nm spheric pores (MC-II) although the specific surface area of MC-III is lower than MC-II and MC-I. The reason might be that the MC-III provides a more favorable pore structure than the other two MCs for flavin based redox reaction at the interface between the biofilm and the electrode. As a result, the MC-III anode delivered the highest power density at around 1700 mW m −2, which is 1.6 fold higher than that of the MC-I anode. A possible mechanism for the pore shape/size dependent interfacial electron transfer process has also been proposed. This work reveals that spheric mesopores with large pore width could be more favorable than the narrow channel-like pores for flavin based interfacial electron transfer in biofilm anodes, which will provide some insights for the design of the mesoporous anode in MFCs.